IgG Seroreactivites to Viral Capsid Protein VP1 of JC and BK Polyomaviruses in Children at Early Ages with Special Reference to Parental Cofactors - Laine Hanna K.; Waterboer Tim; Syrjänen Kari; Grenman Seija; Louvanto Karolina; Syrjänen Stina (MDPI, 2025)
BK (BKPyV) and JC (JCPyV) polyomaviruses are widespread in humans. Transmission at an early age and the role of parents in spreading these viruses through the family are incompletely understood. Our aim was to determine the seroprevalence of BKPyV and JCPyV in infants at the age of 1, 2, 6, 12, 24, and 36 months and to assess the frequency of BKPyV and JCPyV seroconversion. A variety of maternal and paternal covariates were also tested as potential predictors of these early childhood infections. We used multiplex serology to analyze antibodies to BKPyV and JCPyV from baseline to 3-year follow-up visits. We observed that there was nearly perfect correlation in BKPyV and JCPyV serum IgG antibody levels between the mother-infant pairs during the first year of the infant’s life. No correlation among BKPyV antibody titers were found in father–child pairs, whereas JCPyV antibody levels of the father and child had a significant correlation at the 2-year follow-up visit. BKPyV infection may be associated with a child’s predisposition to allergy. In conclusion, after the decay of maternal antibodies, children start to develop their own immunity toward BKPyV and JCPyV, and horizontal transmission of infection in the family can occur.